العملة المشفرة طبيعتها القانونية والتحديات المواجهة لها - أحمد, د. مصطفى محمد (Sulaimani Journal for Humanities, 2023)
This research deals with a legally important topic, which is: "The encrypted currency, its legal nature and the challenges facing it (Bitcoin as an example)", this topic has a great weight and role, and it is not feasible for any country to ignore the encrypted currency and not disclose it, and not to develop working mechanisms to regulate it, as happened at the beginning of its emergence by some countries, and they recently were forced to issue laws regulating its work, after it caused monetary, legal and security problems, so it was necessary to raise awareness. This research came to introduce the encrypted currency (Bitcoin as an example), its legal nature, and the challenges facing it. The researcher first reviewed the emergence of the encrypted currency and its trading mechanism and the Blockchain system, then touched on the Bitcoin currency in terms of: its definition, its concept, and how it works, in addition to addressing the meaning of mining and its mechanism of action, and if it is considered as real money or not, and if it is included in the financial significance or not, and then she expanded on mentioning the disagreement and differing opinions on this issue, citing some examples that support this context, and then talked about smart contracts and the extent of the mechanism of applying the contractual system to the Bitcoin currency. The last part of the research came about the challenges facing the Bitcoin currency, its advantages and dangers, and the obstacles that stand against it, with mentioning of some examples of countries agreeing and rejecting it.
Keywords: Encrypted currency Bitcoin BLOCKCHAIN system mining legal nature smart contracts challenges advantages dangers countries